Dialogic teaching and students' discursive identity negotiation in the learning of science. (April 2017) - Kumpulainen, Kristiina; Rajala, Antti
Abstract: This study sought to understand how dialogic teaching, as enacted in everyday classroom interaction, affords students opportunities for identity negotiation as learners of science. By drawing on sociocultural and sociolinguistic accounts, the study examined how students' discursive identities were managed and recognized in the moment and over time during dialogic teaching and what consequences these negotiations had for their engagement in science learning. The study used video data of classroom interactions collected from an elementary science learning project and placed a specific analytic focus on four students in particular. The results reveal evidence of a rich variety of discursive identities exposed during dialogic teaching, thus demonstrating how the students' identity negotiations were configured according to the social architecture of classroom discourse. Addressing the temporal dimension of dialogic teaching points out critical shifts in the students' discursive identities, of which identification is argued to be pivotal when creating equitable science learning opportunities. Highlights: The study examined students' discursive identities in dialogic science teaching. Students' discursive identities varied according to classroom interaction. The results reveal critical shifts in students' discursive identities. The study shows the value of researching discursive identities in science education.